2017
DOI: 10.1063/1.4973682
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermal transport in polymer composites with percolating networks of silver thin films by the flash diffusivity method

Abstract: The flash diffusivity method, also known as laser flash analysis (LFA), is commonly used to obtain the thermal diffusivity (a) and thermal conductivity (j) of materials, due to its relative simplicity, rapid measurements, small sample size requirement, and standardized commercially available instruments. In this work, an epoxy adhesive was filled with a large fraction of homogeneous micron-sized polymethylmethacrylate spheres coated with thin silver films, such that a percolating metallic network that dominate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…The thermal transport by electrons is limited to occur within the silver thin films or by tunneling across ultrathin epoxy layers between two AgPS. The thermal transport of the AgPS-ICA system has been discussed previously in the context of LF measurements 22 , which concluded that the thermal transport in the AgPS is dominated by the electronic heat transfer in the Ag layer. We believe a minor thermal transport mechanism deserves mention, which is the possibility of electronphonon interactions across the Ag-polymer interfaces.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The thermal transport by electrons is limited to occur within the silver thin films or by tunneling across ultrathin epoxy layers between two AgPS. The thermal transport of the AgPS-ICA system has been discussed previously in the context of LF measurements 22 , which concluded that the thermal transport in the AgPS is dominated by the electronic heat transfer in the Ag layer. We believe a minor thermal transport mechanism deserves mention, which is the possibility of electronphonon interactions across the Ag-polymer interfaces.…”
Section: Resultsmentioning
confidence: 95%
“…For the 45 and 50AgPS sample, the SS measurements give thermal conductivities that are 46 % and 38 % above the 3ω measurements, respectively. Pettersen et al 22 did LF measurements of AgPS-ICAs, and showed that the technique for measuring the specific heat had a significant effect on the measured thermal conductivity for this sample system. However, this effect alone can not explain the large discrepancies observed between the transient and steady state methods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations